The Tapping-PROMS: A test for the assessment of sensorimotor rhythmic abilities - Georgi, Markus; Gingras, Bruno; Zentner, Marcel (Frontiers in Psychology, 2023)
Sensorimotor synchronization is a longstanding paradigm in the analysis of isochronous beat tapping. Assessing the finger tapping of complex rhythmic patterns is far less explored and considerably more complex to analyze. Hence, whereas several instruments to assess tempo or beat tapping ability exist, there is at present a shortage of paradigms and tools for the assessment of the ability to tap complex rhythmic patterns. To redress this limitation, we developed a standardized rhythm tapping test comprising test items of different complexity. The items were taken from the rhythm and tempo subtests of the Profile of Music Perception Skills (PROMS), and administered as tapping items to 40 participants (20 women). Overall, results showed satisfactory psychometric properties for internal consistency and test-retest reliability. Convergent, discriminant, and criterion validity correlations fell in line with expectations. Specifically, performance in rhythm tapping correlated more strongly with performance in rhythm perception than in tempo perception, whereas performance in tempo tapping was more strongly correlated with performance in tempo than rhythm perception. Both tapping tasks were only marginally correlated with non-temporal perception tasks. In combination, the tapping tasks explained variance in external indicators of musical proficiency above and beyond the perceptual PROMS tasks. This tool allows for the assessment of complex rhythmic tapping skills in about 15 minutes, thus providing a useful addition to existing music aptitude batteries.